Iphone all-in-one for dummies, 4th edition - Hutsko, Joe. (John Wiley and Sons, 2014)
In this book, the authours try to find the balance between simple, practical information for new users and new information for experienced users. Whatever your iphone user level, we want this book to bring you a point of using your iphone at the maximum potential for you. For some that might mean using three or four apps such as phone, camera, messages, whereas for others, it might mean using most of the preinstailled apps.